Geographical analysis of the low success rates of the sixth preparatory students in the city of Kut for the period (2015 – 2019) )A study of population geography( - Mohammed Abed, Qasim (Journal of College of Education, 2020)
The research aims to study the low rates of success among students in the sixth year of middle school and to know the reasons behind this, as the results achieved by schools in the city of Kut were characterized by decline and decline in recent years, this study tended to verify the hypothesis of the research that there is a significant decline in success rates Among students, there are many reasons that caused this decline and decline.The results showed that there is a difference in the rates of success between the literary and scientific branches and between males and females, despite their decline in general, and the study tended to adopt the results of the field study to determine the economic and social characteristics of students ’families, some of which had an important impact on their lower levels of education, as well as the main reasons that were It has a role in this decline, the most important of which is the poor use of the Internet and the large number of holidays.
Keywords: )Low, success rates, sixth preparatory, Population